Simulated versus traditional occupational therapy placements: A randomised controlled trial. (31st August 2018) - Imms, Christine; Froude, Elspeth; Chu, Eli Mang Ye; Sheppard, Loretta; Darzins, Susan; Guinea, Stephen; Gospodarevskaya, Elena; Carter, Rob; Symmons, Mark A.; Penman, Merrolee; Nicola‐Richmond, Kelli; Gilbert Hunt, Susan; et al.
Abstract : Background/aim: Professional practise placements in occupational therapy education are critical to ensuring graduate competence. Australian occupational therapy accreditation standards allow up to 200 of a mandated 1000 placement hours to include simulation‐based learning. There is, however, minimal evidence about the effectiveness of simulation‐based placements compared to traditional placements in occupational therapy. We evaluated whether occupational therapy students completing a 40 hour (one week block) Simulated Clinical Placement (SCP) attained non‐inferior learning outcomes to students attending a 40 hour Traditional Clinical Placement (TCP). Methods: A pragmatic, non‐inferiority, assessor‐blinded, multicentre, randomised controlled trial involving students from six Australian universities was conducted. Statistical power analysis estimated a required sample of 425. Concealed random allocation was undertaken with a 1:1 ratio within each university. Students were assigned to SCP or TCP in one of three settings: vocational rehabilitation, mental health or physical rehabilitation. SCP materials were developed, manualised and staff training provided. TCPs were in equivalent practice areas. Outcomes were assessed using a standardised examination, unit grades, the Student Practice Evaluation Form‐Revised and student confidence survey. A generalised estimating equation approach was used to assess non‐inferiority of the SCP to the TCP. Results: Of 570 randomised students (84% female), 275 attended the SCP and 265 the TCP ( n  = 540, 94.7% retention). There were no significant differences between the TCP and SCP on (i) examination results (marginal mean difference 1.85, 95% CI: 0.46–3.24; P  = 0.087); (ii) unit score (mean (SD) SCP: 71.9 (8.8), TCP: 70.34 (9.1); P  = 0.066); or (iii) placement fail rate, assessed using the Student Practice Evaluation Form‐Revised (100% passed both groups). Conclusion: Students can achieve equivalent learning outcomes in a 40 hour simulated placement to those achieved in a 40 hour traditional placement. These findings provide assurance to students, educators and professional accreditation bodies that simulation can be embedded in occupational therapy education with good effect.